PEMBINAAN AWAL BUMDES SEBAGAI MEDIA STRATEGIK PERKEMBANGAN BISNIS PELAKU UMKM DI PACITAN - Ignatius Roni Setyawan; Indra Listyarti (PROSIDING SERINA, 2021)
One way to accelerate the development of the financial aspects of MSME actors is to join BUMDES. This is because there have been many BUMDES that have been established in various regions in Indonesia and in line with Ministerial Regulation no. 4 of 2015 then BUMDES can function as a driving force for the potential of MSME actors. As an agreement with the BUMDES partner Arjuna Mulya, Arjowinangun Village, Pacitan, the form of this PKM activity is an interactive webinar with BUMDES administrators and the community of SMEs in Pacitan online on October 16, 2021 which has an output target of innovative work programs from BUMDES Arjuna Mulya. The BUMDES innovative work program hopes to raise the potential of the MSME industry in Pacitan so that at least it can be widely recognized as being included in the BI MSME database which can also function as a market place. PKM activities carried out on October 16, 2021 include three parts, namely 1) Introduction to the potential of BUMDES to raise the economy of the local community; 2) Social and commercial aspects of BUMDES to further explore the unique potential of MSME actors and certain communities and 3) Conduct digital marketing simulations by Instagram for MSME actors and local communities who have an interest in optimizing their business performance through social media. At the end of the activity, there can also be a two-way question and answer session with Mr. Suparno (village official) who has a longing to further develop the Pacitan culinary business which is managed by his wife through Instagram media. The business only operates at full capacity for the New Year and Eid al-Fitr. Mr. Suparno's aspirations were accommodated by Mr. Handarbeni (Founder of Cardig.In) who promised to provide digital marketing (instagram) training and this became an important outcome of PKM.